(untitled) (Hungarian Journal of Industry and Chemistry, 2011)
We worked out a mathematical modell for the production geometry and mathematical analysis of spiroid worm gear drives. This modell is adapted for analysis of spiroid worm gear drives with random profile. Using this modell it could be possible for defining of the equations of cog surfaces, the surface normal vector, contact curves and connection surface in one concrete case.